Application of response surface methodology for optimizing transesterification of Moringa oleifera oil: Biodiesel production - Rashid, Umer (Elsevier B.V., 2011)
Response surface methodology (RSM), with central composite rotatable design (CCRD), was used to explore optimum conditions for the transesterification of Moringa oleifera oil. Effects of four variables,reaction temperature (25–65 C), reaction time (20–90 min), methanol/oil molar ratio (3:1–12:1) and catalyst concentration (0.25–1.25 wt.% KOH) were appraised. The quadratic term of methanol/oil molar ratio, catalyst concentration and reaction time while the interaction terms of methanol/oil molar ratio with reaction temperature and catalyst concentration, reaction time with catalyst concentration exhibited significant effects on the yield of Moringa oil methyl esters (MOMEs)/biodiesel, p < 0.0001 and p < 0.05, respectively. Transesterification under the optimum conditions ascertained presently by RSM: 6.4:1 methanol/oil molar ratio, 0.80% catalyst concentration, 55 C reaction temperature and 71.08 min reaction time offered 94.30% MOMEs yield. The observed and predicted values of MOMEs yield showed a linear relationship. GLC analysis of MOMEs revealed oleic acid methyl ester, with contribution of 73.22%, as the principal component. Other methyl esters detected were of palmitic, stearic, behenic and arachidic acids. Thermal stability of MOMEs produced was evaluated by thermogravimetric curve. The fuel properties such as density, kinematic viscosity, lubricity, oxidative stability, higher heating value, cetane number and cloud point etc., of MOMEs were found to be within the ASTM D6751 and EN 14214 biodiesel standards.